Yet More Ways to Skin a Definite Integral. (1st January 2016) - Bradie, Brian
Summary: Continuing a topic from two recent articles, we present three additional methods for evaluating a particular definite integral, using partial fractions from complex roots, an infinite series representation beyond Taylor series, and special functions. We discuss what further topics students can explore after becoming familiar with each method. We also present a generalization of the original problem and extensions.